Factors influencing coping skills of middle-aged adults in COVID-19, South Korea - Gu, Minkyung; Woo, Heeyoung; Sok, Sohyune (Frontiers in Public Health, 2024)
Background In light of the persistent COVID-19 pandemic, there is a compelling imperative to enhance the COVID-19 coping capacity among middle-aged adults within the South Korean population. Consequently, there is a need for further research endeavors in this area. Objective This study aims to explore and identify the factors influencing the coping skills of middle-aged adults in COVID-19, South Korea. Methods This study used a cross-sectional descriptive design. Participants were 147 middle-aged adults living in Seoul, Geounggi-do, and Chungchung-do in South Korea. Data included demographics, coping skills, the impact of the event, perceived health status, psychological wellbeing, and family support. The data were analyzed using the SPSS Statistics 25.0 program. Data were collected from March to July 2020. Results The regression model was significant (F = 13.56, p < 0.001), and the adjusted R-squared representing the explanatory power of the model was 0.63. The strongest predictor was perceived health status (β = 0.34), followed by family support (β = 0.31), impact of event (β = −0.24), underlying disease (β = −0.13), and economic status (β = 0.11). Conclusion This study suggests that to improve the coping skills of middle-aged adults with COVID-19, their perceived health status and family support should be strengthened, and the impact of the event should be decreased. Also, it needs that underlying diseases are managed and economic status is improved. Nurses need to pay more attention to the influencing factors to improve the coping skills of middle-aged adults in COVID-19, South Korea.